Analysis of the Implementation of Project Based Learning (PjBL) by Utilizing YouTube Media in Speaking Learning - Hapsari, Estuning Dewi; Rizaldy, Dedy Richi; Sari, Dian Etika; Winarsih, Eni (Journal of Science and Education (JSE), 2026)
This study aims to describe the speaking skills of class 2B students by applying PjBL and the use of youtube media. The research uses a qualitative descriptive approach. The data collection method consists of observation, interviews, and tests. The research subjects of the 2nd semester Accounting Study Program students were 21 students. The data analysis techniques include reduction, presentation, conclusion drawn, and verification. The results of the study stated that students' speaking skills were relatively good. Students are able to complete projects in theory and practice well. The value of speaking practice from linguistic and non-linguistic elements in good qualifications.